2018
DOI: 10.1093/pm/pnx328
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Multicenter, Double-Blind, Parallel Pilot Study Assessing the Effect of Mechanical Adhesiolysis vs Adhesiolysis with Corticosteroid and Hyaluronidase Administration into the Epidural Space During Epiduroscopy

Abstract: A significant improvement of leg and back pain was found in both groups after six months. ODI was significantly improved only in group B in both the six- and 12-month intervals. Back pain at one-year follow-up was only improved in group B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Two articles were RCTs, 36,37 three were prospective‐, 38–40 and four were retrospective 41–44 observational studies. Together, they included 392 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles were RCTs, 36,37 three were prospective‐, 38–40 and four were retrospective 41–44 observational studies. Together, they included 392 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Together, they included 392 patients. Results from one of the RCTs are reported per study arm because both study arms included mechanical adhesiolysis with different targeted drug treatment regimens 37 . For further study characteristics, see Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of SCS is that some patients have reported complications, such as lead migration, local wound infection, pocket pain, loss of therapeutic effects, and cerebrospinal fluid leak with headache; these do not occur with ESP block [4]. Epiduroscopy is another option that may allow the physician to directly visualize the adhesions in the epidural space; this has also been reported to be effective [15]. However, this procedure is more invasive than ESP block and can only be performed at specialized institutions, particularly in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, endoscopic adhesiolysis was shown to be more effective for lumbar PLS in the short term (<6 months) than in the long term (>6 months) [20]. Specifically, the ODI values were restored to baseline in most of the patients at the one-year follow-up in another study [21]. Similarly, the present results showed that the number of responders at the one-and six-month follow-up was 47 (32.0%) and 33 (22.4%), respectively ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%